2019
DOI: 10.1002/acm2.12806
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of HU threshold for coronary artery calcium scans reconstructed at 0.5‐mm slice thickness using iterative reconstruction

Abstract: Purpose This work investigated the simultaneous influence of tube voltage, tube current, body size, and HU threshold on calcium scoring reconstructed at 0.5‐mm slice thickness using iterative reconstruction (IR) through multivariate analysis. Regression results were used to optimize the HU threshold to calibrate the resulting Agatston scores to be consistent with those obtained from the conventional protocol. Methods A thorax phantom set simulating three different body sizes was used in this study. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…29 Hou et al demonstrated good correlation between Agatston scoring on a 3 mm slice thickness image compared to Agatston scoring on a 0.5 mm slice thickness image. 30 Our simulation was limited to 0.5 mm slice thickness which is expected to provide more accurate and sensitive comparisons for Agatston scoring. Nonetheless, future studies might provide insights by varying the slice thickness, and this study is limited without a direct comparison to Agatston scoring at the gold standard slice thickness of 3 mm.…”
Section: Discussionmentioning
confidence: 99%
“…29 Hou et al demonstrated good correlation between Agatston scoring on a 3 mm slice thickness image compared to Agatston scoring on a 0.5 mm slice thickness image. 30 Our simulation was limited to 0.5 mm slice thickness which is expected to provide more accurate and sensitive comparisons for Agatston scoring. Nonetheless, future studies might provide insights by varying the slice thickness, and this study is limited without a direct comparison to Agatston scoring at the gold standard slice thickness of 3 mm.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the problem of increased image noise, iterative reconstruction (IR) was used [24]. IR has been proven to substantially reduce image noise [25,26] and to reduce blooming artifacts [27,28] resulting in higher image quality.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed method could be applied for any site- or software-specific dose level and reconstruction method (eg, kernel, slice thickness, noise reduction algorithm, 24 or keV selection for a dual-energy CT reconstruction). All these factors impact the detected area for each HU scale threshold and should be explored in future work via both phantom study and patient scans to evaluate the clinical performance of the proposed method.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, setting the model 2 thresholds on a scoring software could also benefit other quantitative calcium scores, such as volume score and mass score, which are based on the conventional 130-HU threshold and therefore suffer a similar interscanner variation because of the spectrum difference. 10,23 The proposed method could be applied for any site-or softwarespecific dose level and reconstruction method (eg, kernel, slice thickness, noise reduction algorithm, 24 or keV selection for a dual-energy CT reconstruction). All these factors impact the detected area for each HU scale threshold and should be explored in future work via both phantom study and patient scans to evaluate the clinical performance of the proposed method.…”
Section: Discussionmentioning
confidence: 99%